Positive Youth Development melalui Olahraga: Systematic Literatur Review - Uyun, Mita Siti Padilah; Ma’mum, Amung; Carsiwan, Carsiwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to determine positive youth development through sport. The method applied in this research is the Systematic Literature Review (SLR) method. The steps in SLR include systematic identification, selection, evaluation and synthesis of existing scientific literature. The protocol used in this SLR is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes). The data used in this research uses the Publish or Perish database with Google Scholar, Scopus and Taylor and Francis online. Based on the results of the search carried out using a systematic literature review, there were 275 documents which then became 7 articles that were included in the final review process. The results of the data identification show that based on the systematic literature review that has been presented, it can be judged that positive youth programs among youth in sports are very important because they can increase their involvement in implementing the program effectively. This shows that the integration of universal sports values in physical education can have a positive impact on the development of adolescent students. Keywords: Positive Youth Development, Sports, Systematic Literature Review